Class and everyday media use - Hovden Jan Fredrik; Rosenlund Lennart (Nordicom Review)
In this article, we consider how contemporary media use is structured by social class, following the theoretical and methodical framework derived from Bourdieu's book Distinction, published in 1984, with a detailed study of everyday use of media platforms, brands, and content among Norwegian citizens (N = 2,064). First, we analyse how such media use varies in the overall social space using multiple correspondence analysis. Second, we independently explore the main differences and groupings of media practices, combining multifactor analysis and cluster analysis. While identifying important gender and generational differences, this study clearly shows how media use inside both younger and older generations are marked by class differences, which we argue demonstrates the fundamental and continuing importance of class for understanding mediated lifestyles.